How to reconcile wood production and biodiversity conservation? The Pan-European boreal forest history gradient as an "experiment". (15th July 2018) - Naumov, Vladimir; Manton, Michael; Elbakidze, Marine; Rendenieks, Zigmars; Priednieks, Janis; Uhlianets, Siarhei; Yamelynets, Taras; Zhivotov, Anton; Angelstam, Per
Abstract: There are currently competing demands on Europe's forests and the finite resources and services that they can offer. Forestry intensification that aims at mitigating climate change and biodiversity conservation is one example. Whether or not these two objectives compete can be evaluated by comparative studies of forest landscapes with different histories. We test the hypothesis that indicators of wood production and biodiversity conservation are inversely related in a gradient of long to short forestry intensification histories. Forest management data containing stand age, volume and tree species were used to model the opportunity for wood production and biodiversity conservation in five north European forest regions representing a gradient in landscape history from very long in the West and short in the East. Wood production indicators captured the supply of coniferous wood and total biomass, as well as current accessibility by transport infrastructure. Biodiversity conservation indicators were based on modelling habitat network functionality for focal bird species dependent on different combinations of stand age and tree species composition representing naturally dynamic forests. In each region we randomly sampled 25 individual 100-km 2 areas with contiguous forest cover. Regarding wood production, Sweden's Bergslagen region had the largest areas of coniferous wood, followed by Vitebsk in Belarus and Zemgale in Latvia. NW Russia's case study regions in Pskov and Komi had the lowest values, except for the biomass indicator. The addition of forest accessibility for transportation made the Belarusian and Swedish study region most suitable for wood and biomass production, followed by Latvia and two study regions in NW Russian. Regarding biodiversity conservation, the overall rank among regions was opposite. Mixed and deciduous habitats were functional in Russia, Belarus and Latvia. Old Scots pine and Norway spruce habitats were only functional in Komi. Thus, different regional forest histories provide different challenges in terms of satisfying both wood production and biodiversity conservation objectives in a forest management unit. These regional differences in northern Europe create opportunities for exchanging experiences among different regional contexts about how to achieve both objectives. We discuss this in the context of land-sharing versus land-sparing. Highlights: Resolving rival demands on Europe's boreal forest requires evidence-based knowledge. Forest history gradients form a natural experiment to assess levels of rivalry. Indicators of wood production and biodiversity conservation were inversely related. Regional differences in northern Europe offer unique opportunities for learning.